Correction: Dual-defect surface engineering of bimetallic sulfide nanotubes towards flexible asymmetric solid-state supercapacitors. Issue 47 (7th December 2020) - Kang, Ling; Zhang, Mengyao; Zhang, Jian; Liu, Shude; Zhang, Nan; Yao, Wenjing; Ye, Yan; Luo, Chen; Gong, Zhiwei; Wang, Chaolun; Zhou, Xiaofeng; Wu, Xing; et al.
Abstract : Correction for 'Dual-defect surface engineering of bimetallic sulfide nanotubes towards flexible asymmetric solid-state supercapacitors' by Ling Kang et al., J. Mater. Chem. A, 2020, DOI: ; 10.1039/d0ta08979f .